(untitled) - Schultz, Brad (Amsterdam ; London, 2005., 2005)
A uniquely comprehensive text, Sports Media emphasizes the skills that you will need in order to be successful in the industry. With extensive coverage on reporting, anchoring, and production, this text offers thorough and effective descriptions of the sports reporter and anchor's function in a broadcast environment.
Keywords: Sports journalism,Báo thể thao